1991
DOI: 10.1002/ijc.2910490303
|View full text |Cite
|
Sign up to set email alerts
|

Changes in glycolipids in human renal‐cell carcinoma and their clinical significance

Abstract: The expression patterns of glycolipids of human renal-cell carcinoma were studied in primary tumors from 23 cases and 5 metastatic lesions from 4 cases using HPTLC (high-performance thin-layer chromatography). The expression pattern of glycolipids in primary tumors was characteristic of the histological cell type. In granular-cell carcinoma, lactosylceramide (CDH), GM3 and the longer-chain gangliosides (gangliosides migrating more slowly than GM3) increased, although in clear-cell carcinoma, CDH and other glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 27 publications
4
35
0
Order By: Relevance
“…RCC biopsies and cell lines show an increase in G m2, G m1, and G d1a types when compared with normal renal tissue. Several authors have correlated altered expression of select gangliosides to tumor progression and metastatic potential (39,40). Ganglioside concentrations are highest in the tumor microenvironment, where they can be shed in the form of micelles or membrane vesicles (25).…”
Section: Figurementioning
confidence: 99%
“…RCC biopsies and cell lines show an increase in G m2, G m1, and G d1a types when compared with normal renal tissue. Several authors have correlated altered expression of select gangliosides to tumor progression and metastatic potential (39,40). Ganglioside concentrations are highest in the tumor microenvironment, where they can be shed in the form of micelles or membrane vesicles (25).…”
Section: Figurementioning
confidence: 99%
“…The one-dimensional NMR spectrum of the simpler compound, G2, clearly displays two characteristic ␣-NeuAc H-3eq resonances at 2.769 and 2.727 ppm, as well as four ␤-anomeric resonances ( 3 J 1,2 ϭ 7-9 Hz) in the downfield region, of which that at 4.512 ppm could be tentatively assigned as the ␤-GlcNAc H-1, that at 4.160 ppm most likely as the ␤-Glc H-1, and those at 4.248 and 4.117 ppm as two ␤-Gal H-1, in agreement with the glycosyl composition analysis. Based on analogy to published NMR data, the rather upfield chemical shift of one of the ␤-Gal H-1 resonances suggested the possibility of a type 1 chain core, as only the terminal ␤-Gal H-1 of Lc 4 Cer has ever been observed upfield of 4.15 ppm (18). Three NAc methyl singlets (1.888, 1.875, and 1.759 ppm) are likewise consistent with the presence of two ␣-NeuAc and one ␤-GlcNAc residue in the ganglioside; moreover, the chemical shifts of the two more downfield singlets suggested the presence of NeuAc in both ␣233 and ␣236 linkages, respectively (10, 17, 20).…”
Section: Glycosyl and Fatty N-acyl Composition Analysis Of Tos-1 Gangmentioning
confidence: 72%
“…An initial study of GSL patterns of renal cell carcinoma (RCC) and its metastatic deposits indicated that enhanced expression of higher gangliosides having TLC mobility similar to or slower than that of GM2 in original RCC tissue is correlated with metastatic potential (4). However, expression of SLe x and dimeric Le x in RCC is higher in differentiated than in undifferentiated form and is not correlated with RCC metastasis (5,6).…”
mentioning
confidence: 99%
“…These changes have direct consequences for cell adhesion, proliferation, and signaling. Many globo-series GSL are important markers for breast, prostate, testicular, and renal cell carcinoma, in which they have been implicated in metastasis and adherence to microvascular tissue (31)(32)(33)(34)(35). Globo-series GSL are also important host factors in the pathophysiology of several infectious diseases (36).…”
Section: Discussionmentioning
confidence: 99%